Changes in different nutrients and enzyme contents in mango leaves infected with Colletotrichum gloesporioides - M. ZAHANGIR ALAM, and N. ABSAR, M. TOFAZZAL HOSSAIN* (Indian Phytopathology, 2002)
Total chlorophyll, chlorophyll a and chlorophyll b content of mango leaves decreased after infection by C. gloeosporioides [Glomerella cingulata] in laboratory tests. Lipid, total sugar and reducing sugar content decreased significantly, while protein, calcium and iron content increased moderately after infection.